Inovasi Pengolahan Limbah Organik Menjadi Pupuk Organik Cair Untuk Mendukung Pertanian Berkelanjutan di Kabupaten Sitaro - Pinaria, Yeanly Wuena; Karuntu, Rilya Patricia Esther; Kanter, Jabes Wolter; Moko, Emma Mauren; Mege, Revolson Alexius; Mewengkang, Alfrina (Servitium Smart Journal, 2025)
Modern agriculture faces challenges in the form of dependence on chemical fertilizers and increasing organic waste that has not been optimally utilized. This activity aims to develop innovation in processing organic waste into liquid organic fertilizer (POC) as part of a sustainable agricultural system in Beong Village, Siau Tagulandang Biaro Islands Regency (SITARO). The implementation method used a Participatory Rural Appraisal (PRA) approach and the application of appropriate technology through training, manufacturing, and POC application tests. The main ingredients consisted of chicken manure, nutmeg leaves, and vegetable waste fermented using EM4 bioactivator for 24 days in two fermentation stages, namely anaerobic and aerobic. The analysis showed that the POC contained 1.14% N, 0.01% P, 0.38% K, pH 6.8, and a C/N ratio of 14.5 in accordance with SNI 19-7030-2004. The application of POC increased the growth of mustard plants by 35% and tomatoes by 32%, and reduced the use of chemical fertilizers by 55%. This innovation reduced the volume of organic waste by 60% and increased farmer group productivity by 70%. The novelty of this activity lies in the integration of local agricultural waste management into economically valuable liquid fertilizer that supports circular economy and low-emission agriculture.